Microstructural characterization of YO ODS-Fe-Cr model alloys - de Castro, V; Marquis, E; Lozano-Perez, S; Jenkins, M; Leguey, T; Muñoz, A; Monge, M; Pareja, R (2009)
Two Fe-12 wt% Cr alloys, one containing 0.4 wt% YO and the other YO-free, have been produced by mechanical alloying followed by hot isostatic pressing. These oxide dispersion strengthened and reference alloys were characterized both in the as-HIPed state and after tempering by transmission electron microscopy and atom-probe tomography. The as-HIPed alloys exhibited the characteristic microstructure of lath martensite and contained a high density of dislocations. Small voids with sizes <10 nm were also observed. Both alloys also contained MC and MC carbides (M = Cr, Fe) probably as a result of C ingress during milling. After tempering at 1023 K for 4 h the microstructures had partially recovered. In the recovered regions, martensite laths were replaced by equiaxed grains in which MC carbides decorated the grain boundaries. In the ODS alloy nanoparticles containing Y were commonly observed within grains, although they were also present at grain boundaries and adjacent to large carbides. © 2009 Elsevier B.V. All rights reserved.